Sugar Crash: Analysis of Diabetes Risk in Office Workers Due to Irregular Work Patterns and Eating Patterns - Hutapea, Albert Manggading; Hutapea, Kimberley Maharani Maulibulung (Oshada, 2025)
This study aims to analyze the risk of type 2 diabetes in office workers affected by sedentary work patterns and irregular eating patterns. Office work tends to require low physical activity, high work pressure, and inconsistent meal times, which can increase the risk of metabolic disorders, including diabetes. This study used a quantitative approach with a survey method of 150 office workers in urban areas, combined with in-depth interviews with 10 key informants. The results showed that 68% of respondents had irregular eating habits and 74% experienced moderate to high work stress. As many as 45% of respondents also showed blood sugar levels that were on the prediabetes threshold. Factors such as consumption of foods high in sugar and carbohydrates, lack of physical activity, and the habit of skipping breakfast contributed significantly to the increased risk of diabetes. These findings emphasize the need for interventions in the form of occupational health education, provision of healthy food in the office environment, and work time arrangements that support a healthy lifestyle. In conclusion, the lifestyle of modern office workers can be a serious risk factor for metabolic health, and requires more comprehensive preventive treatment.